Scanning elastic lidar observations of aerosol transport in New York City - Diaz Adrian; Dominguez Victor; Dobryansky Selma; Wu Yonghua; Arend Mark; Vladutescu Daniela Viviana; Gross Barry; Moshary Fred (EPJ Web of Conferences, 2018)
In this study, spatial distribution of aerosols in New York City is observed using a scanning eyesafe 532 nm elastic-backscatter micro-pulse lidar system. Observations show dynamics of the boundary layer and inhomogeneous distribution and transport of aerosols. The data acquired are complemented with simultaneous measurements of particulate matter and wind speed and direction. Furthermore, the system observations are validated by comparing them with a colocated multi-wavelength lidar.